If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 15 = 7x + -9 Reorder the terms: 15 + x = 7x + -9 Reorder the terms: 15 + x = -9 + 7x Solving 15 + x = -9 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 15 + x + -7x = -9 + 7x + -7x Combine like terms: x + -7x = -6x 15 + -6x = -9 + 7x + -7x Combine like terms: 7x + -7x = 0 15 + -6x = -9 + 0 15 + -6x = -9 Add '-15' to each side of the equation. 15 + -15 + -6x = -9 + -15 Combine like terms: 15 + -15 = 0 0 + -6x = -9 + -15 -6x = -9 + -15 Combine like terms: -9 + -15 = -24 -6x = -24 Divide each side by '-6'. x = 4 Simplifying x = 4
| 4n=944 | | 4=x/13+1 | | 7x+3y=37 | | 4a+3=6a+12 | | 23=-1+6(3x-2) | | 7n-4n+11n= | | 4x+21=5x+10 | | 8(3)=v | | 11c+21=-24 | | 4(cos^2)x+7(sinx)-7=0 | | -8(4+4n)=-288 | | 4(cos^2)x+7sinx-7=0 | | -39+7k=2(7k+3)+2k | | 53=-2-(1-7n) | | 3*x+3=30 | | 50y+25x= | | y=-2x+22 | | 29t=319 | | 17+x=18*x | | 2(x+8)+7=43 | | x^3-12x^2+35= | | -6=-(p-1) | | 4p-8p+4p+6= | | 0=1960t-4.9t^2-h | | 9+(-2-8)=X | | x^2+44+16x=180 | | X^2-8x+10= | | 9=1+8(1+n) | | (W-2)(w+7)= | | 5(3+5x)=-85 | | 3y+2=-2y-7 | | 3[x-2]=-9 |